The north–south gap and spillover effect of Chinese service industry green development - Chen, Baoqi; Xu, Xiaotong (Frontiers in Ecology and Evolution, 2023)
Taking the Qinling-Huaihe River as the boundary, this paper divides the Chinese service industry into north and south regions. The current study calculates the green total factor productivity of the Chinese service industry from 2003 to 2019 by using the DEA-Malmquist productivity index method. The influencing factors of the service industry in the north and south of China are tested by the Moran index and the spatial Durbin model. The results show that the green total factor productivity of the Chinese service industry shows great regional heterogeneity. The average green total factor productivity of northern China is 1.4 percentage points lower than that of southern China. The leading factor for the growth of green total factor productivity in southern China is technological progress, while TFP in northern China mainly depends on technical efficiency improvement. The results of spatial econometric regression show that the intensive level of producer services plays a significant role in promoting the green development of the service industry. The transportation infrastructure can significantly promote the green development level of the service industry. Finally, some suggestions are provided to narrow the gap between the north and south of the Chinese service industry.